Liquid crystalline block copoly(etherester)s - Pietkiewicz, D.; Rosłaniec, Z. (Polimery, 2022)
A review with 99 references covering the sinthesis and characteristic of copoly(ether-ester)s which contain a liquid-crystal polyester segment.The effect of the nature and proportion of hard segments and soft segments on the liquid-crystal behavior of copolymers is described.